PERANAN TAX PLANNING DALAM EFISIENSI PEMBAYARAN PAJAK PENGHASILAN PT. ACE HARDWARE TBK (Students' Journal of Accounting and Banking, 2014)
This study aims to get the differences of the commercial profit and the fiscal profit, and efficiency of company income tax payments before and after application of tax planning in enterprises. This research takes data from a retail company that listed on the Indonesian Stock Exchange in the Consolidated Financial Statements of 5 years from the 2009 – 2013. Data is processed and analyzed through a process of the fiscal reconciliation, t-test and test hypotheses. The results of this research are among the commercial and fiscal profit there was no significant difference, the application of tax planning in company also does not cause the efficiency of tax to be paid by the company.Keywords: Commercial Profit, Fiscal Profit, Fiscal Reconciliation, Tax Indebted (PPh), Eefficiency, Tax Planning